Comparative Genomic Analysis of Citrobacter and Key Genes Essential for the Pathogenicity of Citrobacter koseri - Yuan, Chao; Yin, Zhiqiu; Wang, Junyue; Qian, Chengqian; Wei, Yi; Zhang, Si; Jiang, Lingyan; Liu, Bin (Frontiers in Microbiology, 2019)
Citrobacter species are opportunistic bacterial pathogens that have been implicated in both nosocomial and community-acquired infections. Among the genus Citrobacter, Citrobacter koseri is often isolated from clinical material, and has been known to cause meningitis and brain abscess in neonates and immunocompromised individuals. The virulence determinants of Citrobacter, however, remain largely unknown. Based on traditional methods, the genus Citrobacter has been divided into 11 species, but this has been problematic. Here, we determined an improved, fine scale, and more accurate phylogeny of the genus Citrobacter based on whole genome sequence data from 129 Citrobacter genomes, 31 of which were sequenced in this study. A maximum likelihood phylogeny constructed with core genome single-nucleotide polymorphisms classified all Citrobacter isolates into 11 distant groups, with all C. koseri strains clustering into a single group. For comprehensive and systematic comparative genomic analyses, we investigated the distribution of virulence factors, resistance genes, and macromolecular secretion systems among the Citrobacter genus. Moreover, combined with group-specific genes analysis, we identified a key gene cluster for iron transport, which is present in the C. koseri group, but absent in other the groups, suggesting that the high-pathogenicity island (HPI) cluster may be important for the pathogenicity of C. koseri. Animal experiments showed that loss of the HPI cluster significantly decreased C. koseri virulence in mice and rat. Further, we provide evidence to explain why Citrobacter freundii is less susceptible than C. koseri to several antibiotics in silico. Overall, our data reveal novel virulence clusters specific to the predominantly pathogenic C. koseri strains, which form the basis for elucidating the virulence mechanisms underlying these important pathogens.